Changes in pancreatic histology, insulin secretion and oxidative status in diabetic rats following treatment with Ficus deltoidea and vitexin - Samsulrizal, Nurdiana; Goh, Yong Meng; Ahmad, Hafandi; Md Dom, Sulaiman; Azmi, Nur Syimal’ain; Noor Mohamad Zin, Noor Syaffinaz; Ebrahimi, Mahdi (BioMed Central, 2017)
Background: The potential application of Ficus deltoidea and vitexin for the management of symptomatologies associated with diabetes mellitus (DM) has gained much attention. However, less firm evidence comes from data to augment our understanding of the role of F. deltoidea and vitexin in protecting pancreatic β-cells. The aim of this study was to assess histological and oxidative stress changes in the pancreas of streptozotocin (STZ)-induced diabetic rats following F. deltoidea extract and vitexin treatment. Methods: F. deltoidea and vitexin was administrated orally to six-weeks STZ-induced diabetic rats over 8 weeks period. The glucose and insulin tolerances were assessed by intraperitoneal glucose (2 g/kg) tolerance test (IPGTT) and intraperitoneal insulin (0.65 U/kg) tolerance test (IPITT), respectively. Subsequently, insulin resistance was assessed by homeostasis assessment model of insulin resistance (HOMA-IR), quantitative insulin sensitivity check index (QUICKI) and the insulin/triglyceride-derived McAuley index. The histological changes in the pancreas were then observed by hematoxylin-eosin (H&E) staining. Further, the pattern of fatty acid composition and infrared (IR) spectra of the serum and pancreas were monitored by gas chromatography (GC) method and Fourier Transform Infrared (FT-IR) spectroscopy. Results: F. deltoidea and vitexin increased pancreatic antioxidant enzymes and promoted islet regeneration. However, a significant increase in insulin secretion was observed only in rats treated with F. deltoidea. More importantly, reduction of fasting blood glucose is consistent with reduced FT-IR peaks at 1200-1000 cm−1. Conclusions: These results accentuate that F. deltoidea and vitexin could be a potential agent to attenuate pancreatic oxidative damage and advocate their therapeutic potential for treating DM.